2019
DOI: 10.1371/journal.pone.0222987
|View full text |Cite
|
Sign up to set email alerts
|

Studying the link between physiological performance of Crotalaria ochroleuca and the distribution of Ca, P, K and S in seeds with X-ray fluorescence

Abstract: This study describes the use of X-ray fluorescence spectroscopy in Crotalaria ochroleuca seed technology. This work evaluated X-ray fluorescence techniques to estimate the physiological performance of different C. ochroleuca seed coat colours based on the concentration and distribution of Ca, P, K, and S in seed structures. The treatments consisted of seeds separated by coat colours (yellow, green, and red) and a control treatment (colour mix according to their natural occurrence in commercial lots), and was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
(37 reference statements)
0
8
0
2
Order By: Relevance
“…Herein, the spatial distributions for both Ca and K recorded in cowpea, soybean, and kidney bean seeds were akin to those found in the cross-sections of Crotalaria ochroleuca seeds [11], another specie from the Fabaceae family. Furthermore, Ca was also found mostly trapped in the tegument of rice ( Oryza sativa ) seeds [26], suggesting that seeds’ nutrient distribution patterns are highly conserved.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Herein, the spatial distributions for both Ca and K recorded in cowpea, soybean, and kidney bean seeds were akin to those found in the cross-sections of Crotalaria ochroleuca seeds [11], another specie from the Fabaceae family. Furthermore, Ca was also found mostly trapped in the tegument of rice ( Oryza sativa ) seeds [26], suggesting that seeds’ nutrient distribution patterns are highly conserved.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, space-resolved nutrient localization revealed that nutrient distribution varies across seed tissues. Particularly, P, S, and Ca were mainly found in the embryonic regions, whereas Ca was found in seed coat and hilum regions of Crotalaria ochroleuca and Arabidopsis thaliana seeds [11,12], whereas beneficial elements, such as Se and Ni, respectively, can be found in the embryo and cotyledon tissues of cowpea ( Vigna unguiculata L.), buckwheat ( Fagopyrum esculentum ), and soybean ( Glycine max (L.) Merrill) [1315]. These few studies lead to the following question: How preserved is this spatial pattern across Families and within Families?…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ On the other hand, S signals are present in both control and plasma-treated grey seeds; however, the S content percentage increased after the plasma treatment. In general, the S and P are present in the embryonic axis 31 , so plasma treatment results in deeper etching on the surface of seed coat layers that revealed with different elemental composition and possibility to increase the concentration of S and P. The primary source of S is the defense compounds like S-rich proteins, glutathione, hydrogen sulfide, phytochelatins, etc., which are crucial for plant survival 32 . Additionally, the phytomelanin pigments of seeds containing S compounds might contribute to increased S concentration 33 after plasma treatment, as plant melanins react with strong oxidizing agents produced during plasma treatment, like H 2 O 2 , O 3 , O 2…”
Section: Resultsmentioning
confidence: 99%
“…Figura 2) e com alto potencial de incorporação de nitrogênio ao sistema(COTRIM et al, 2019; PACHECO et al, 2015;CASTRO;MAGALHÃES, 2018).…”
unclassified
“…considerada uma planta rústica, má hospedeira de nematoides, com raízes profundas e eficientes na ruptura das camadas mais adensadas do solo, tolerante ao estresse hídrico e sensível ao fotoperíodo, uma vez que com o encurtamento dos dias começa a florescer(BERTÉ et al, 2010;COTRIM et al, 2019;MASCARENHAS; WUTKE, 2014; PACHECO et al, 2015).A C. ochroleuca é normalmente cultivada em consórcio, rotação e sucessão com várias culturas, como soja, milho, cana-de-açúcar (PACHECO et al, 2015;RUGARE;PIETERSE; …”
unclassified